Efeketivitas pembuatan bioetanol sebagai sumber green energy dari buah mangga klonal 21 (Mangifera indica) dengan pengaruh lama fermentasi dan massa ragi: Effectiveness of making bioethanol as a source of green energy from clonal mango fruit 21 (Mangifera indica L.) with the effect of fermentation time and yeast mass - Deny Utomo; Rendika Octa Pratama (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2024)
Mango fruit is a horticultural commodity in Pasuruan district which has various types and varieties that are abundant, but this fruit is rarely processed into an innovation. Mango fruit can be made into bioethanol, so it will be a useful renewable energy. Indonesia has great potential to develop green energy because of the abundance of natural resources that can be utilized. This study aims to determine the effect and optimal proportion of bioethanol to the mass of yeast and the length of time fermemtasi. The research method used a factorial Randomized Block Design with 3 treatment factors, namely yeast mass (1%, 3%, 5%) and factor 2 fermentation time (48 hours and 96 hours). The factors and treatments were 6 treatment combinations, each treatment was carried out 3 times. The variables studied included chemical parameters (ethanol content value, sugar content value, pH value and water content) and visual combustion parameters. Data analysis for chemical parameters was analyzed using ANOVA statistics, followed by Fisher's test. The best treatment of chemical analysis using the De Garmo Effectiveness Index method. The best treatment was found in the treatment combination R3T2 (5% yeast mass and fermentation time 96 hours) with chemical parameters including ethanol content of 50%, sugar content of 17%, pH 4.3 and moisture content of 0.98%.